UTILIZATION OF FISH PROTEIN HYDROLYSATE AS A NITROGEN SOURCE IN FERMENTED MEDIA OF CEPHALOSPORIN C PRODUCTION BY ACREMONIUM CHRYSOGENUM Biomcc 00141 - Fatonah, Ani Fatonah; Saepudin, Endang; Suyanto (BRIN - Badan Riset dan Inovasi Nasional, 2024)
Optimizing Indonesia's maritime resources as an effort to reduce reliance on imported raw materials for the pharmaceutical industry. This study investigates the use of fish protein hydrolysate, derived from trash fish flour, as a supplement in the fermentation process for producing cephalosporin C. This key raw material is used to create cephalosporin antibiotics through fermentation with the fungus Acremonium chrysogenum Biomcc 0141. Hydrolysate from trash fish flour is obtained through an enzymatic hydrolysis process using a protease found in pineapple hump extract which was optimized. The results of hydrolysis optimization on hydrolysate from trash fish flour produce a protein content of 3.37%. The protein hydrolysate obtained is then used in the cephalosporin C fermentation process. The addition of trash fish protein hydrolysate to cephalosporin C fermentation media showed a significant increase in the productivity of cephalosporin C, which is up to 85.39% higher than the fermentation process without the addition of fish protein hydrolysates.